Synthesis and Antiinflammatory Activity of 1-Aralkyl-2-Aryl-benzimidazoles - Ahmad Khan, Suroor; Vishani, Sandeep; Ishratullah, K. (Asian Journal of Chemistry, 2010)
In the present work, we describe the synthesis and antiinflammatoryactivity of 1-aralkyl-2-aryl benzimidazoles.